The experience of France regarding legal regulation of public-private partnership as a basis for the improvement of ukrainian legislation - Banakh , Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is devoted to the study of the existing problem of institutional functioning of public-private partnership in Ukraine, the absence of PPP mechanisms with quasi-private entities, such as mixed economy communities (SEM) or quasi-public enterprises (SAEMES), and the absence of a single body in the field of PPP.To confirm the existence of problems in the field of low popularity of the PPP mechanism, the author provides statistics on the annual implementation of projects in Ukraine and other countries, such as Great Britain and France. Citing these figures, the author mentions the problem of the uncertainty of the Ukrainian approach to following the experience of the Anglo-Saxon or Romano-Germanic legal system. In addition, the article emphasizes the absence of a regulated mechanism for providing PPP projects with government guarantees and the absence of the possibility of reimbursing the private partner’s investments when the contract is changed at the initiative of the state partner.The author proposes to apply the experience of France and implement the mechanisms of public-private partnership with quasi-public enterprises, using the example of infrastructure development in Paris to establish a parking system. The author also draws on the experience in Cannes, where PPPs with quasi-public entities were used to improve the work of the museum.At the same time, it is emphasized that it is worth taking into account the lessons learned by France when implementing PPPs with quasi-public entities, such as the need to strengthen personnel specializing in contractual PPP obligations, the need to define a new model of approach to payments to a private partner – namely, regular provision of payments and subsidies to the private partner.The lack of government guarantees to ensure wider implementation of projects in the field of public-private partnership is also proposed to be resolved by adopting additional by-laws. The author paid special attention to the existence of a service body in the field of PPP in France – MAPPP. The author emphasizes that despite the fact that this body has numerous functions in France, in Ukraine such a body could become the only «service» PPP body.